Radial Transport of Nutrients: The Plant Root as a Polarized Epithelium. Issue 2 (18th August 2014) - Barberon, Marie; Geldner, Niko
Abstract : Different routes underlie radial transport of nutrients in plant roots and are influenced by the endodermis permeability and the polarity of transporters . Abstract: In higher plants, roots acquire water and soil nutrients and transport them upward to their aerial parts. These functions are closely related to their anatomical structure; water and nutrients entering the root first move radially through several concentric layers of the epidermis, cortex, and endodermis before entering the central cylinder. The endodermis is the innermost cortical cell layer that features rings of hydrophobic cell wall material called the Casparian strips, which functionally resemble tight junctions in animal epithelia. Nutrient uptake from the soil can occur through three different routes that can be interconnected in various ways: the apoplastic route (through the cell wall), the symplastic route (through cellular connections), and a coupled trans-cellular route (involving polarized influx and efflux carriers). This Update presents recent advances in the radial transport of nutrients highlighting the coupled trans-cellular pathway and the roles played by the endodermis as a barrier.